Phase I dose-escalation study of the mTOR inhibitor sirolimus and the HDAC inhibitor vorinostat in patients with advanced malignancy - Park, Haeseong (Oncotarget, 2016)
Preclinical models suggest that histone deacetylase (HDAC) and mammalian target of rapamycin (mTOR) inhibitors have synergistic anticancer activity. We designed a phase I study to determine the safety, maximum tolerated dose (MTD), recommended phase II dose (RP2D), and dose-limiting toxicities (DLTs) of combined mTOR inhibitor sirolimus (1 mg-5 mg PO daily) and HDAC inhibitor vorinostat (100 mg-400 mg PO daily) in patients with advanced cancer. Seventy patients were enrolled and 46 (66%) were evaluable for DLT assessment since they completed cycle 1 without dose modification unless they had DLT. DLTs comprised grade 4 thrombocytopenia (n = 6) and grade 3 mucositis (n = 1). Sirolimus 4 mg and vorinostat 300 mg was declared RP2D because MTD with sirolimus 5 mg caused significant thrombocytopenia. The grade 3 and 4 drug-related toxic effects (including DLTs) were thrombocytopenia (31%), neutropenia (8%), anemia (7%), fatigue (3%), mucositis (1%), diarrhea (1%), and hyperglycemia (1%). Of the 70 patients, 35 (50%) required dose interruption or modification and 61 were evaluable for response. Partial responses were observed in refractory Hodgkin lymphoma (−78%) and perivascular epithelioid tumor (−54%), and stable disease in hepatocellular carcinoma and fibromyxoid sarcoma. In conclusion, the combination of sirolimus and vorinostat was feasible, with thrombocytopenia as the main DLT. Preliminary anticancer activity was observed in patients with refractory Hodgkin lymphoma, perivascular epithelioid tumor, and hepatocellular carcinoma.